Daily Sun‐induced chlorophyll fluorescence vs. irradiance curves reflect the photoadaptation of phytoplankton in surface waters - Yannick Huot; David Antoine; Vincenzo Vellucci (Limnology and Oceanography, 2025)
Phytoplankton chlorophyll Sun‐induced fluorescence is observable in the upwelling light field of the ocean. This allows its observation by radiometers in situ or on satellite sensors. Since it is influenced by both biomass and physiology it can potentially provide information about both. Since fluorescence yield is complementary to photosynthesis and heat in photosystem II, its observation throughout the day provides information on the response of phytoplankton to diel light cycles. Here we use a time series collected in the northwestern Mediterranean Sea (BOUSSOLE site) to extract photophysiological parameters of phytoplankton using the Sun‐induced fluorescence and as well as with an active chlorophyll fluorometer. The daily resolved patterns are consistent with photoacclimation and photoadaptation processes and reflect seasonal variations of the mixed‐layer average irradiance. We also show that fluorescence yields derived from satellite measurements (MODIS) at the same location are not correlated to these patterns, confirming the limited influence of photoacclimation and photoadaptation on the satellite‐derived chlorophyll fluorescence yield near solar noon.